1984
DOI: 10.1002/mawe.19840151004
|View full text |Cite
|
Sign up to set email alerts
|

Notch‐Size Effect in fatigue of steel specimens – verification of some calculation methods

Abstract: New, more accurate fatigue test results were used for verification of different calculation methods and for establishing a more reliable relationship between the notch factor and the notch radius. Scatter bands for the dependence of the notch sensitivity KF/KT on the notch radius were obtained for steel specimens with stress concentration factors KT ≤ 3.6, with particular consideration of test results for large component similar specimens with large notch radii. The scatter bands of test points were ploted sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…After extensive comparison of experimental and numerical results, Buch (1984) concluded that the estimates of notch size effect according to one-parameter formulas are mostly quite conservative and are also in disagreement with some trends observed for notch sensitivity of steels. Recent work by Ciavarella and Meneghetti (2004) has shown that the classical Peterson's (1959) relation results in fatigue notch factor that approaches unity when the notch root radius tends to zero regardless of the actual notch or crack size, thus completely neglecting the existence of notch size effect.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…After extensive comparison of experimental and numerical results, Buch (1984) concluded that the estimates of notch size effect according to one-parameter formulas are mostly quite conservative and are also in disagreement with some trends observed for notch sensitivity of steels. Recent work by Ciavarella and Meneghetti (2004) has shown that the classical Peterson's (1959) relation results in fatigue notch factor that approaches unity when the notch root radius tends to zero regardless of the actual notch or crack size, thus completely neglecting the existence of notch size effect.…”
Section: Introductionmentioning
confidence: 77%
“…The Neuber and Peterson equations are the first order attempts to incorporate materials length scale in describing notch sensitivity via the socalled material constant; typically a function of the tensile strength of the material. While a single parameter involving a critical distance may be a viable approach, notch size effects arising from deformation and damage phenomena may render an elementary simple single parameter approach like critical distance inapplicable (Buch 1984;Qylafku et al 1999;Ciavarella and Meneghetti 2004;Lanning et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Notch influences are generally specified by the fatigue notch factor K f representing the ratio of the unnotched to the notched fatigue resistance. A study in [2] provides an overview and verification of several models evaluating K f for different base materials. Engineering feasible concepts are mostly based on the relative stress gradient ' due to an efficient automated evaluation of finite element results.…”
Section: T Imentioning
confidence: 99%
“…Neuber's hypothesis and variants of his hypothesis proposed by other investigators form the basis for flaw tolerance analysis. See, for example [8], a reference that makes comparisons among the Neuber-Kuhn, Peterson, Heywood, Stieler-Siebel and the Buch-Switek formulas, all proposed for the prediction of the effects of fillets, characterized by a radius, and notches, characterized by a depth, a notch angle and radius, on the fatigue limit.…”
Section: Definitionmentioning
confidence: 99%